2021
DOI: 10.3389/fmicb.2021.659602
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the Intestinal Microbial Community and Transcriptome Profile in Common Carp (Cyprinus carpio L.)

Abstract: In a previous study, we found that the growth performance of the new strain of Huanghe carp is related to gene expression and bacterial community in the gut. In order to better understand the relationship between the gene expression level and bacterial abundance in the gut, we studied the growth performance, gut bacterial structure, and transcriptome profile in the 4th generation of the new carp strain (selection group) at harvesting time, and compared them with the control line (traditional Huanghe carp). Bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…To determine significant differences in β-diversity among different field strains, PERMANOVA was carried out using the "adonis" function of the VEGAN package 49 . Spearman correlation between genes transcripts, LC 50 of each insecticide (All data were used in correlation analysis between insecticide susceptibilitytranscriptome-microbiome, only field strains data were used in environmental abiotic factors correlation analysis because we do not have information on their origins or environment histories) and microbial abundance (bacteria and fungi) was calculated using corAndPvalue 50 in WGCNA package (version 1.69) and P was corrected by Benjamini and Hochberg FDR (BH) method, set threshold as P(adj) < 0.05 in subsequent use to remove weak interactions 51 . The network was made in Gephi (version 0.9.2) based on the spearman correlation metrics.…”
Section: Discussionmentioning
confidence: 99%
“…To determine significant differences in β-diversity among different field strains, PERMANOVA was carried out using the "adonis" function of the VEGAN package 49 . Spearman correlation between genes transcripts, LC 50 of each insecticide (All data were used in correlation analysis between insecticide susceptibilitytranscriptome-microbiome, only field strains data were used in environmental abiotic factors correlation analysis because we do not have information on their origins or environment histories) and microbial abundance (bacteria and fungi) was calculated using corAndPvalue 50 in WGCNA package (version 1.69) and P was corrected by Benjamini and Hochberg FDR (BH) method, set threshold as P(adj) < 0.05 in subsequent use to remove weak interactions 51 . The network was made in Gephi (version 0.9.2) based on the spearman correlation metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The gut of common carp carries symbiotic bacteria. Thus, removing gut contents during germ cell processing may release bacteria into the body cavity, which can contaminate germ cell cultures (19). To address this issue, we have compared two methods to dissect and open the body cavity of common carp.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of the human intestinal microbiota in regulating host gene expression and manipulating the microbiome composition may be useful in future treatments (Richards et al, 2019). Other studies have also confirmed that the intestinal microbiota and the host intestinal epithelium should be regarded as an interrelated entity (Shi et al, 2021) and that the percentages of Aeromonas and Rosemonas and the differential expression of IL12 are associated with the disease resistance of Huanghe carp to new strains (Su et al, 2021). Our results indicated that some of the top 10 differentially expressed genes related to the genus level of intestinal microorganisms were involved in the immune response, such as cell adhesion molecule 1 (CADM1) and thrombospondin-4-b (thbs4b).…”
Section: Relationship Between the Degs And Bacterial Community Compos...mentioning
confidence: 93%